A theory of power in software ecosystems formed by small-to-medium enterprises - SANTOS, George Augusto Valença (2016)
Context: the emergence of software ecosystems has changed the dynamics of software industry in the last decade. An ecosystem consists of a set of businesses functioning as a unit and interacting with a shared market for software and services, together with the relationships involving them. Software ecosystems originate in partnerships among software companies as a strategy to acquire complementary skills and features, obtain new customers, as well as divide R&D costs. In this setting, partner companies rely on each other for survival and effectiveness, which generates a network of dependent actors and a flow of power among them. Aims: the goal of this research is to develop a substantive theory to explain how power and dependence manifest in partnerships among small-to-medium enterprises (SMEs) building a software ecosystem. This result enables us to describe the dynamics of partnerships in this environment, since power is a base atomic particle of relationships. Method: we performed two exploratory case studies of software ecosystems formed by SMEs. We collected rich qualitative data from eight software companies by means of twenty-seven semi-structured interviews. In addition, we considered companies’ internal documents, field notes and web-based data. Thematic analysis was adopted to organise and describe the data set. The results were interpreted in light of a theoretical framework underpinned by French and Raven’s power taxonomy and later refined in six confirmatory interviews with the companies. Finally, we performed a cross-case analysis to synthesise our findings and build the theory. Results: the resultant theory, called PRM-SECO, highlights the interactions among different power forms in addition to their correspondent source(s) in the software ecosystem. It reveals that (1) power is fluid in a software ecosystem formed by SMEs; (2) pool of customers and skill/knowledge are the most frequent power sources; (3) expert power is the fundamental power form that triggers most power capabilities held by SMEs; (4) reward power attaches the partner and is often exercised by SMEs; (5) coercive power disturbs the partnerships and is rarely exercised by SMEs; (6) referent power tends to supersede other power forms and is rarely held by SMEs; and (7) legitimate power is the most frequent power form exercised by SMEs. Conclusion: this theory provides a better understanding on how power and dependence influence the behaviour and coordination of companies within a software ecosystem. The particular focus on SMEs complements the state-of-art, since most research in the field concerns mature ecosystems governed by big players such as SAP and Apple. It is a useful lens for researchers to explore ecosystem partnerships. In addition, it is a valuable tool for companies to analyse power distribution, have insights on how to evolve their participation in the network and define sustainable strategies for ecosystem governance.